All-solid-state lithium battery and preparation method thereof

By using the second halide solid electrolyte Li3MCl6-xBrx as the barrier layer in a solid lithium battery, a dense layer is formed through heat treatment, which solves the problem of lithium dendrites, improves the cycle performance and safety of the battery, and reduces the inside of the battery Obstacle.

CN119133580APending Publication Date: 2024-12-13SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411271082.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The generation and growth of lithium dendrites in solid-state lithium-ion batteries lead to short-circuiting of the battery, and high-voltage assembly increases the defects of solid-state electrolyte particles, affecting the safety and circulation performance of the battery.

Method used

The second halide solid electrolyte Li3MCl6-xBrx is introduced as a barrier layer in a solid lithium battery. It is transformed from solid state to liquid state and then to solid state through heat treatment to form a dense barrier layer, inhibiting the growth of lithium dendrites and improving ionic conductivity to reduce interface impedance.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, reduce the probability of battery short circuit, improve cycle performance and safety performance, and reduce battery internal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038712870000201
    Figure BDA0005038712870000201
  • Figure BDA0005038712870000211
    Figure BDA0005038712870000211
Patent Text Reader

Abstract

The invention relates to an all-solid-state lithium battery and a preparation method thereof. The all-solid-state lithium battery comprises a positive electrode, a negative electrode, a solid electrolyte membrane and a barrier layer arranged between the negative electrode and the solid electrolyte membrane, the solid-state electrolyte membrane comprises a first halide solid-state electrolyte, the barrier layer comprises a second halide solid-state electrolyte, the chemical general formula of the second halide solid-state electrolyte is Li3MCl6-xBrx, M is a trivalent metal ion, 0 lt; xlt; 6; and the second halide solid electrolyte in the barrier layer is converted from a solid state to a liquid state and then is converted from the liquid state to the solid state. According to the all-solid-state lithium battery provided by the invention, the dense barrier layer comprising the second halide solid electrolyte is arranged between the negative electrode and the solid electrolyte membrane, so that the growth of lithium ions in the solid-state lithium ion battery is effectively inhibited, and meanwhile, the ionic conductivity is improved, the interface impedance is reduced, and the internal resistance of the battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an all-solid-state lithium battery and a preparation method thereof. Background Art

[0002] Traditional liquid lithium-ion batteries have received widespread attention in terms of safety due to the use of flammable and explosive electrolytes. Solid-state lithium-ion batteries are considered to be the next generation of battery products with industrialization capabilities due to their higher safety.

[0003] Since the electrodes and solid electrolyte membranes in solid-state lithium-ion batteries are in solid-solid contact, the battery is formed by pressing at a relatively high pressure. On the one hand, the solid electrolyte membrane is generally formed by squeezing solid particles against each other. Affected by the particle size and hardness of the solid electrolyte particles, the solid electrolyte membrane cannot be dense. Therefore, when lithium dendrites are generated due to uneven deposition of lithium ions in the battery, the lithium dendrites can grow along the pores of the solid electrolyte membrane, that is, the gaps between the solid electrolyte powders, causing a short circuit between the positive and negative electrodes. On the other hand, since the positive and negative electrodes and the solid electrolyte membrane are assembled by pressing, the higher pressure will further increase the defects of the solid electrolyte particles, inducing the generation and growth of lithium dendrites. Therefore, the problem of lithium dendrites in solid-state lithium-ion batteries cannot be ignored. Summary of the invention

[0004] Based on this, it is necessary to provide an all-solid-state lithium battery and a preparation method thereof, which can effectively inhibit the growth of lithium ions in solid-state lithium-ion batteries, while improving ionic conductivity, reducing interface impedance, and lowering battery internal resistance.

[0005] The first aspect of the present application provides an all-solid-state lithium battery, which includes a positive electrode, a negative electrode, a solid electrolyte membrane, and a barrier layer disposed between the negative electrode and the solid electrolyte membrane; the solid electrolyte membrane includes a first halide solid electrolyte, the barrier layer includes a second halide solid electrolyte, and the chemical formula of the second halide solid electrolyte is: Li3MCl 6-x Br x , where M is a trivalent metal ion, 0 <x<6;;

[0006] The second halide solid electrolyte in the barrier layer changes from solid to liquid, and then changes from liquid to solid.

[0007] In some embodiments, Li3MCl 6-x Br x The melting point is 80℃~200℃.

[0008] In some embodiments, M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe3+ , Y 3+ Sc 3+ 、Bi 3+ and one or more of trivalent lanthanide metals.

[0009] In some embodiments, Li3MCl 6-x Br x The ionic conductivity λ satisfies: λ ≥ 1mS / cm.

[0010] In some embodiments, the porosity of the barrier layer is between 0.1% and 10%.

[0011] In some embodiments, the barrier layer has a thickness of 2 μm to 20 μm.

[0012] In some embodiments, the barrier layer further includes a second component, the second component forms a skeleton structure, and satisfies: the melting point of the second component is greater than the melting point of the second halide solid electrolyte.

[0013] In some embodiments, the second component includes one of a ceramic material and a polymer material.

[0014] In some embodiments, the solid electrolyte membrane further includes a second halide solid electrolyte.

[0015] In some embodiments, the mass proportion of the second halide solid electrolyte in the solid electrolyte membrane is 5% to 40%.

[0016] The second aspect of the present application provides a method for preparing the all-solid-state lithium battery of the first aspect, the method comprising the following steps:

[0017] Preparation of positive electrode, negative electrode and solid electrolyte membrane;

[0018] Spraying or laying the barrier layer powder onto one of the negative electrode and the solid electrolyte membrane, and subjecting the mixture to hot pressing to obtain an intermediate; or, preparing the barrier layer, and subjecting the barrier layer and one of the negative electrode and the solid electrolyte membrane to hot pressing to obtain an intermediate;

[0019] The intermediate is bonded to the other of the negative electrode and the solid electrolyte membrane and the positive electrode to obtain an all-solid-state lithium battery.

[0020] In some embodiments, the temperature of the hot pressing treatment is 120° C. to 180° C.; and / or, the time of the hot pressing treatment is 0.5 min to 20 min; and / or, the pressure of the hot pressing treatment is 10 MPa to 500 MPa.

[0021] Compared with the traditional technology, this application has at least the following beneficial effects:

[0022] The all-solid-state lithium battery provided by the present application is provided with a second halide solid electrolyte Li3MCl between the negative electrode and the solid electrolyte membrane. 6-x Br x The barrier layer, and Li3MCl 6-x Br x It has a lower melting point than other halide solid electrolytes, which is beneficial for the second halide solid electrolyte in the barrier layer to transform from solid to liquid, and then from liquid to solid, thereby significantly improving the density of the barrier layer. The dense barrier layer can also effectively inhibit the growth of lithium dendrites generated at the negative electrode along the grain boundaries of the solid electrolyte, reducing the probability of battery short circuit, thereby improving the cycle performance of the lithium battery.

[0023] In addition, thanks to the second halide solid electrolyte Li3MCl 6-x Br x It has high ionic conductivity, which is conducive to the good transmission of lithium ions between the solid electrolyte membrane and the negative electrode. When the barrier layer is formed on the surface of the negative electrode, it can effectively improve the contact between the barrier layer and the negative electrode and reduce the interface resistance between the barrier layer and the negative electrode, thereby effectively reducing the internal resistance of the battery.

[0024] Furthermore, when the solid electrolyte membrane contains a second halide solid electrolyte Li3MCl 6-x Br x When the interface impedance between the barrier layer and the solid electrolyte membrane is reduced, DETAILED DESCRIPTION

[0025] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0026] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0027] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0028] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0029] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0031] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0032] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0033] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0034] The first aspect of the present application provides an all-solid-state lithium battery, which includes a positive electrode, a negative electrode, a solid electrolyte membrane, and a barrier layer disposed between the negative electrode and the solid electrolyte membrane. The solid electrolyte membrane includes a first halide solid electrolyte, the barrier layer includes a second halide solid electrolyte, and the chemical formula of the second halide solid electrolyte is: Li3MCl 6-x Br x, wherein M is a trivalent metal ion, and 0 < x < 6. The second halide solid electrolyte in the barrier layer changes from solid state to liquid state and then from liquid state to solid state. Specifically, by performing heat treatment on the second halide solid electrolyte, the heat treatment temperature is greater than or equal to the melting point of the second halide solid electrolyte, and the second halide solid electrolyte melts at high temperature and solidifies at low temperature.

[0035] The applicant found that Li3MCl 6-x Br x has a relatively low melting point compared to other halide solid electrolytes, which is beneficial for the second halide solid electrolyte in the barrier layer to change from solid state to liquid state and then from liquid state to solid state, thereby significantly improving the denseness of the barrier layer. The dense barrier layer can also effectively inhibit the growth of lithium dendrites generated at the negative electrode along the gaps between the solid electrolyte particles, reducing the probability of battery short circuit, and further improving the safety performance and cycling performance of the lithium battery.

[0036] In some embodiments, the melting point of the second halide solid electrolyte is 80 °C to 200 °C, including but not limited to 80 °C, 100 °C, 120 °C, 140 °C, 160 °C, 180 °C, 200 °C.

[0037] In some embodiments, M is selected from one or more of Ga 3+ , In 3+ , Al 3+ , Fe 3+ , Y 3+ , Sc 3+ , Bi 3+ and trivalent lanthanide metals.

[0038] In some embodiments, the value range of x satisfies: 2 < x < 5.

[0039] It can be understood that by adjusting the value range of x, that is, adjusting the doping concentration of bromide ions, the distribution of bromide ions and chloride ions in the crystal lattice is optimized, thereby further reducing the melting point of Li3MCl 6-x Br x , and reducing the preparation difficulty of the barrier layer.

[0040] In some embodiments, the lithium stability of the second halide solid electrolyte is better than that of the first halide solid electrolyte.

[0041] Further, the potential of the second halide solid electrolyte to lithium after reduction is 0.01V to 0.4V, and the potential of the first halide solid electrolyte to lithium after reduction is 0.5V to 2V. Exemplarily, the potential of the second halide solid electrolyte Li3InCl3Br3 to lithium after reduction is 0.05V, and the potential of the first halide solid electrolyte Li2ZrCl6 to lithium after reduction is 1.4V; by providing a barrier layer including the second halide solid electrolyte between the negative electrode and the solid electrolyte membrane, and providing a barrier layer between the solid electrolyte membrane and the negative electrode, the direct contact between the solid electrolyte membrane and the negative electrode can be effectively reduced, and the first halide solid electrolyte in the solid electrolyte membrane can be prevented from being reduced by the negative electrode, resulting in deterioration of the cycle performance of the battery.

[0042] Herein, "stability to lithium" refers to the property of not reacting with lithium metal to form interfacial byproducts with low ionic conductivity or electronic conductivity. The lower the potential of the solid electrolyte to lithium after reduction, the stronger its stability to lithium.

[0043] In some embodiments, the barrier layer is disposed on the solid electrolyte membrane, on a side close to the negative electrode.

[0044] In some embodiments, the barrier layer is disposed on the negative electrode, on a side close to the solid electrolyte membrane. When the barrier layer is formed on the surface of the negative electrode, the second halide solid electrolyte has a certain fluidity when in a liquid state, and partially enters between the particles of the electrode material on the surface of the negative electrode, which can effectively increase the contact area between the barrier layer and the negative electrode, reduce the interface resistance between the barrier layer and the negative electrode, and thus effectively reduce the internal resistance of the battery.

[0045] In some embodiments, the porosity of the barrier layer is 0.1% to 10%, including but not limited to 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. Within the above porosity range, the dense barrier layer can effectively inhibit the growth of lithium dendrites generated by the negative electrode along the grain boundaries of the solid electrolyte, further reducing the probability of battery short circuit.

[0046] In some embodiments, the thickness of the barrier layer is 2 μm to 20 μm, including but not limited to 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, and 20 μm. Within the above thickness range, the path length of the lithium ion channel is appropriate, while reducing the internal resistance of the battery, a certain mechanical strength is guaranteed, the growth of lithium dendrites is further inhibited, the barrier effect of the barrier layer is better played, and the stability of the negative electrode interface is further improved. Furthermore, the thickness of the barrier layer is 5 μm to 18 μm.

[0047] In some embodiments, the barrier layer further includes a second component, and the second component has a melting point greater than a melting point of the second halide solid electrolyte.

[0048] In some embodiments, the mass ratio of the second component in the barrier layer is 0.1% to 20%, including but not limited to 0.1%, 0.5%, 1%, 3%, 5%, 7%, 9%, 10%, 12%, 14%, 16%, 18%, 20%. Within the above mass ratio range, the mechanical properties and safety are improved while reducing the internal resistance of the battery. Further, the mass ratio of the second component in the barrier layer is 1% to 10%.

[0049] In some of the embodiments, the second component has better stability to lithium than the first halide solid electrolyte.

[0050] In some of these embodiments, the second component includes one or more of a ceramic material and a polymer material.

[0051] In some embodiments, the ceramic material is selected from one or more of aluminum oxide, zirconium dioxide, titanium dioxide, silicon dioxide, magnesium oxide, and barium titanate.

[0052] In some embodiments, the polymer material is selected from one or more of polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polyimide (PI), polycarbonate (PC), aramid, and cellulose.

[0053] In some of the embodiments, the second component forms a skeleton structure, and the second halide solid electrolyte is dispersed in the skeleton structure. The skeleton structure of the barrier layer further improves the mechanical properties of the barrier layer, further inhibits the growth of lithium dendrites, and has high safety performance. The second halide solid electrolyte is dispersed in the skeleton structure to form a dense barrier layer, further reducing the interface impedance and the internal resistance of the battery. Exemplarily, the polymer material can form a skeleton by means such as electrospinning.

[0054] In the present application, the type of the first halide solid electrolyte is not particularly limited, and any known halide solid electrolyte can be used in the present application without violating the inventive concept of the present application. This is only an illustrative example and not a limitation on the scope of protection.

[0055] Exemplarily, the first halide solid electrolyte includes a basic halide solid electrolyte such as Li2ZrCl6, Li3InCl6, Li3YCl6, or a halide solid electrolyte obtained by doping and modifying the above basic halide solid electrolyte.

[0056] In some embodiments, the solid electrolyte membrane further comprises a second halide solid electrolyte. Adding the second halide solid electrolyte material to the solid electrolyte membrane improves the interface compatibility between the solid electrolyte membrane and the barrier layer, improves the interface contact performance, and effectively reduces the interface impedance between the barrier layer and the solid electrolyte membrane.

[0057] In some embodiments, the mass proportion of the second halide solid electrolyte in the solid electrolyte membrane is 5% to 40%, including but not limited to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%. Further, the mass proportion of the second halide solid electrolyte in the solid electrolyte membrane is 15% to 25%.

[0058] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or more of Li-In alloy, graphite, and silicon-carbon composite material.

[0059] In some embodiments, in the negative electrode active material layer, the mass percentage of the negative electrode active material is 80 wt %-98 wt %.

[0060] In some embodiments, the negative electrode further includes a negative electrode binder, and the negative electrode binder includes one or more of polyvinyl alcohol, styrene-butadiene rubber, polyvinylidene fluoride, sodium alginate, polyacrylic acid, polyimide, lithium polyacrylate, and sodium hydroxymethyl cellulose.

[0061] In some embodiments, in the negative electrode active material layer, the mass percentage of the negative electrode binder is 1 wt %-10 wt %.

[0062] In some embodiments, the negative electrode further includes a negative electrode conductive agent, and the negative electrode conductive agent includes one or more of carbon black, graphite, carbon nanotubes, and graphene.

[0063] In some embodiments, in the negative electrode active material layer, the mass percentage of the negative electrode conductive agent is 1 wt %-10 wt %.

[0064] In some embodiments, the positive electrode includes a positive electrode collector and a positive electrode active material layer located on at least one side of the positive electrode collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a ternary positive electrode material, a lithium manganese-rich positive electrode material, lithium cobalt oxide, lithium nickel manganese oxide, lithium iron phosphate, and lithium manganese iron phosphate.

[0065] In some embodiments, in the positive electrode active material layer, the mass percentage of the positive electrode active material is 80 wt %-99.8 wt %.

[0066] In some embodiments, the positive electrode further includes a positive electrode conductive agent.

[0067] In some embodiments, the positive electrode conductor includes graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and from the aspect of improving conductivity, the positive electrode conductor may preferably be superconducting carbon black.

[0068] In some embodiments, the specific surface area of ​​the positive electrode conductive agent can be 80 m 2 / g~200m 2 / g, preferably 100m 2 / g~150m 2 / g.

[0069] In some embodiments, in the positive electrode active material layer, the mass percentage of the positive electrode conductive agent is 0.1 wt %-10 wt %.

[0070] In some embodiments, the positive electrode further includes a positive electrode binder.

[0071] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber and fluororubber, preferably polytetrafluoroethylene. It should be noted that the selection of the positive electrode binder in this application is related to the melting point of the halide solid electrolyte, and should satisfy: the melting point temperature of the positive electrode binder is greater than the melting point temperature of the halide solid electrolyte.

[0072] In some preferred embodiments, the binder comprises a fiberized binder. It is understood that the fiberized binder can be transformed from a granular state to a fibrous state under the action of a high shear force.

[0073] Exemplarily, the fiberized binder includes one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene (PE), and polypropylene (PP).

[0074] In some embodiments, in the composite positive electrode, the thickness of the positive electrode active layer may be 30 μm to 400 μm, for example, 30 μm, 40 μm, 50 μm, 80 μm, 110 μm, 200 μm, 300 μm, 400 μm, preferably 50 μm to 110 μm.

[0075] The second aspect of the present application provides a method for preparing the all-solid-state lithium battery of the first aspect, the method comprising the following steps:

[0076] S1. Prepare positive electrode, negative electrode and solid electrolyte membrane;

[0077] S2, spraying or laying the barrier layer powder onto one of the negative electrode and the solid electrolyte membrane, and heat-pressing the barrier layer to obtain an intermediate; or, preparing the barrier layer, and heat-pressing the barrier layer and one of the negative electrode and the solid electrolyte membrane to obtain an intermediate;

[0078] S3. Bonding the intermediate to the negative electrode, the other of the solid electrolyte membrane and the positive electrode to obtain an all-solid-state lithium battery.

[0079] In some embodiments, in step S2, the barrier layer powder only includes the second halide solid electrolyte.

[0080] In some embodiments, in step S2, the barrier layer powder includes a second halide solid electrolyte and a ceramic material.

[0081] In some of the embodiments, in step S2, the polymer material is spun to form a skeleton, and the second halide solid electrolyte is dispersed in the skeleton to prepare the barrier layer.

[0082] The preparation method of the all-solid-state lithium battery provided in the present application forms a barrier layer by heat pressing treatment. The second halide solid electrolyte in the barrier layer changes from solid to liquid during the heat pressing treatment, and then changes from liquid to solid after cooling, so that it flows on the interface with the negative electrode or the solid electrolyte membrane, thereby improving the surface smoothness of the barrier layer, improving the interface contact with the solid electrolyte membrane or the negative electrode, reducing the interface impedance, and thus reducing the internal resistance of the battery.

[0083] In some embodiments, the temperature of the hot pressing treatment is 120°C to 180°C, including but not limited to 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, and 180°C. Within the above temperature range, the second halide solid electrolyte of the barrier layer is ensured to melt during the preparation process, which not only ensures a certain fluidity, thereby improving the interface contact and reducing the interface impedance, but also ensures the structural integrity of the formed barrier layer. Further, the temperature of the hot pressing treatment is 135°C to 165°C.

[0084] In some embodiments, the heat pressing treatment time is 0.5 min to 20 min, including but not limited to 0.5 min, 2 min, 4 min, 6 min, 8 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min. Further, the heat pressing treatment time is 6 min to 15 min.

[0085] In some embodiments, the pressure of the hot pressing treatment is 10 MPa to 500 MPa, including but not limited to 10 MPa, 50 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa. Further, the pressure of the hot pressing treatment is 50 MPa to 300 MPa.

[0086] In the present application, the hot pressing treatment method can adopt hot pressing with a double-roller device, or other hot pressing treatment methods that can realize the inventive concept of the present application, and are not particularly limited here.

[0087] The present application will be further described below with reference to specific embodiments and comparative examples.

[0088] Example 1

[0089] In a first aspect, the present embodiment provides an all-solid-state lithium battery, comprising a positive electrode, a negative electrode, a solid electrolyte membrane, and a barrier layer disposed between the negative electrode and the solid electrolyte membrane.

[0090] The solid electrolyte membrane uses the first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3InCl3Br3 and the binder PTFE, and the barrier layer uses the second halide solid electrolyte Li3InCl3Br3. The melting point of the second halide solid electrolyte Li3InCl3Br3 is 120°C. The barrier layer is arranged at the negative electrode, on the side close to the solid electrolyte membrane.

[0091] In a second aspect, this embodiment provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0092] (1) Preparation of positive electrode: NCM811, PTFE, super-P, and Li2ZrCl6 are mixed uniformly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, subjected to fiberization treatment, to form a first mixed material, and the first mixed material is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the time is 10 minutes, and the pressure is 120Mpa;

[0093] (2) Preparation of negative electrode: The negative electrode active materials graphite, (CMC+SBR), super-P and Li3YCl3Br3 are mixed evenly in a mass ratio of 69:4:2:25, placed in a high shear force equipment mixer, fiberized to form a second mixture, and the second mixture is rolled to form a first negative electrode layer; the rolling temperature is 60°C and the rolling time is 5 minutes; the negative electrode current collector and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode. The hot-pressing temperature is 120°C, the time is 12 minutes, and the pressure is 200MPa;

[0094] (3) Preparation of solid electrolyte membrane: The first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3InCl3Br3 and the binder PTFE were mixed in a mass ratio of 73:25:2, and then pressed into a membrane;

[0095] (4) Spraying the barrier layer powder of the second halide solid electrolyte Li3InCl3Br3 onto the negative electrode, performing a heat pressing process to form a barrier layer, and obtaining an intermediate.

[0096] The temperature of the hot pressing treatment is 150° C., the pressure of the hot pressing treatment is 250 MPa, and the time of the hot pressing treatment is 10 min.

[0097] (5) Bonding the intermediate to the solid electrolyte membrane and the positive electrode to obtain an all-solid-state lithium battery.

[0098] Example 2

[0099] In a first aspect, the present embodiment provides an all-solid-state lithium battery, comprising a positive electrode, a negative electrode, a solid electrolyte membrane, and a barrier layer disposed between the negative electrode and the solid electrolyte membrane.

[0100] The solid electrolyte membrane uses the first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3InCl3Br3 and the binder PTFE, and the barrier layer uses the second halide solid electrolyte Li3InCl3Br3. The melting point of the second halide solid electrolyte Li3InCl3Br3 is 120°C. The barrier layer is arranged on the solid electrolyte membrane, on the side close to the negative electrode.

[0101] In a second aspect, this embodiment provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0102] (1) Preparation of positive electrode: NCM811, PTFE, super-P, and Li2ZrCl6 are mixed uniformly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, subjected to fiberization treatment, to form a first mixed material, and the first mixed material is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode layer are stacked, hot-pressed, and cooled to form a composite positive electrode. The hot-pressing temperature is 150°C, the time is 10 minutes, and the pressure is 120 MPa;

[0103] (2) Preparation of negative electrode: The negative electrode active materials graphite, (CMC+SBR), super-P and Li3YCl3Br3 are mixed evenly in a mass ratio of 69:4:2:25, placed in a high shear force equipment mixer, fiberized to form a second mixture, and the second mixture is rolled to form a first negative electrode layer; the rolling temperature is 60°C and the rolling time is 5 minutes; the negative electrode current collector and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode. The hot-pressing temperature is 120°C, the time is 12 minutes, and the pressure is 200MPa;

[0104] (3) Preparation of solid electrolyte membrane: The first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3InCl3Br3 and the binder PTFE were mixed in a mass ratio of 65:25:10, and then pressed into a membrane;

[0105] (4) Spraying the barrier layer powder of the second halide solid electrolyte Li3InCl3Br3 onto the solid electrolyte membrane, performing a heat pressing treatment to form a barrier layer, and obtaining an intermediate.

[0106] The temperature of the hot pressing treatment is 150° C., the pressure of the hot pressing treatment is 250 MPa, and the time of the hot pressing treatment is 10 min.

[0107] (5) Bonding the intermediate to the solid electrolyte membrane and the positive electrode to obtain an all-solid-state lithium battery.

[0108] Example 3

[0109] In a first aspect, the present embodiment provides an all-solid-state lithium battery, comprising a positive electrode, a negative electrode, a solid electrolyte membrane, and a barrier layer disposed between the negative electrode and the solid electrolyte membrane.

[0110] The solid electrolyte membrane uses the first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3InClBr5 and the binder PTFE, and the barrier layer uses the second halide solid electrolyte Li3InClBr5. The melting point of the second halide solid electrolyte is 120°C. The barrier layer is arranged at the negative electrode, on the side close to the solid electrolyte membrane.

[0111] In a second aspect, this embodiment provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0112] (1) Preparation of positive electrode: NCM811, PVDF and super-P were mixed in a solvent NMP at a mass ratio of 95:3:2, and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was coated on the surface of aluminum foil, dried, cold pressed, cut and slit to obtain a positive electrode sheet;

[0113] (2) Preparation of negative electrode: The negative electrode is a Li-In alloy. Lithium sheets and In sheets are cut into the size of the battery, rolled together, and added during battery assembly;

[0114] (3) Preparation of solid electrolyte membrane: The first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3InClBr5 and the binder PTFE were mixed in a mass ratio of 73:25:2, and then pressed into a membrane;

[0115] (4) Spraying the barrier layer powder of the second halide solid electrolyte Li3InClBr5 onto the negative electrode, performing a hot pressing process to form a barrier layer, and obtaining an intermediate.

[0116] The temperature of the hot pressing treatment is 150° C., the pressure of the hot pressing treatment is 250 MPa, and the time of the hot pressing treatment is 10 min.

[0117] (6) The intermediate is bonded to a solid electrolyte membrane and a positive electrode to obtain an all-solid-state lithium battery.

[0118] Example 4

[0119] In a first aspect, the present embodiment provides an all-solid-state lithium battery, comprising a positive electrode, a negative electrode, a solid electrolyte membrane, and a barrier layer disposed between the negative electrode and the solid electrolyte membrane.

[0120] The solid electrolyte membrane uses the first halide solid electrolyte Li2ZrCl6 and the second halide solid electrolyte Li3In 0.5 Fe 0.5 Cl3Br3 and binder PTFE, the barrier layer uses the second halide solid electrolyte Li3In 0.5 Fe 0.5 Cl3Br3 and the second component polyvinylidene fluoride PVDF. The second halide solid electrolyte Li3In 0.5 Fe 0.5 The melting point of Cl3Br3 is 125° C. The barrier layer is arranged on the negative electrode, on the side close to the solid electrolyte membrane, and the mass proportion of the second component in the barrier layer is 3%.

[0121] In a second aspect, this embodiment provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0122] (1) Preparation of positive electrode: NCM811, PVDF and super-P were mixed in a solvent NMP at a mass ratio of 95:3:2, and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was coated on the surface of aluminum foil, dried, cold pressed, cut and slit to obtain a positive electrode sheet;

[0123] (2) Preparation of negative electrode: The negative electrode is a Li-In alloy. Lithium sheets and In sheets are cut into the size of the battery, rolled together, and added during battery assembly;

[0124] (3) Preparation of solid electrolyte membrane: The first halide solid electrolyte Li2ZrCl6 and the second halide solid electrolyte Li3In 0.5 Fe 0.5 Cl3Br3 and binder PTFE were mixed in a mass ratio of 73:25:2 and then pressed into a film;

[0125] (4) Preparation of the first barrier layer powder: PAN is electrospun to form a matrix, and the second halide solid electrolyte Li3In 0.5 Fe 0.5 Cl3Br3 is dispersed in the matrix.

[0126] (5) The first barrier layer powder and the negative electrode are hot pressed to obtain an intermediate.

[0127] The temperature of the hot pressing treatment is 150° C., the pressure of the hot pressing treatment is 250 MPa, and the time of the hot pressing treatment is 10 min.

[0128] (6) The intermediate is bonded to a solid electrolyte membrane and a positive electrode to obtain an all-solid-state lithium battery.

[0129] Example 5

[0130] In the first aspect, the present embodiment provides an all-solid-state lithium battery, including a positive electrode, a negative electrode, a solid electrolyte membrane, and a barrier layer disposed between the negative electrode and the solid electrolyte membrane, wherein the solid electrolyte membrane is selected from a first halide solid electrolyte Li2ZrCl6, a second halide solid electrolyte Li3In 0.5 Fe 0.5 Cl3Br3 and binder PTFE, the barrier layer uses the second halide solid electrolyte Li3In 0.5 Fe 0.5 Cl3Br3 and the second component aluminum oxide Al2O3. The second halide solid electrolyte Li3In 0.5 Fe 0.5The melting point of Cl3Br3 is 125° C. The barrier layer is arranged on the negative electrode, on the side close to the solid electrolyte membrane, and the mass proportion of the second component in the barrier layer is 3%.

[0131] In a second aspect, this embodiment provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0132] (1) Preparation of positive electrode: NCM811, PVDF and super-P were mixed in a solvent NMP at a mass ratio of 95:3:2, and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry was coated on the surface of aluminum foil, dried, cold pressed, cut and slit to obtain a positive electrode sheet;

[0133] (2) Preparation of negative electrode: The negative electrode is a Li-In alloy. Lithium sheets and In sheets are cut into the size of the battery, rolled together, and added during battery assembly;

[0134] (3) Preparation of solid electrolyte membrane: The first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3YCl3Br3 and the binder PTFE were mixed in a mass ratio of 73:25:2, and then pressed into a membrane;

[0135] (4) Preparation of barrier layer powder: The second halide solid electrolyte Li3YCl3Br3, the second component aluminum oxide and the binder PTFE were mixed in a mass ratio of 94:3:3.

[0136] (5) The barrier layer powder is spread on the negative electrode, and a barrier layer is formed by heat pressing to obtain an intermediate.

[0137] The thickness of the barrier layer is 10 μm, the temperature of the hot pressing treatment is 150° C., the pressure of the hot pressing treatment is 250 MPa, and the time of the hot pressing treatment is 10 min.

[0138] (6) The intermediate is bonded to a solid electrolyte membrane and a positive electrode to obtain an all-solid-state lithium battery.

[0139] Comparative Example 1

[0140] This embodiment provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0141] (1) Preparation of positive electrode: NCM811, PTFE, super-P, and Li2ZrCl6 are mixed uniformly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, subjected to fiberization treatment, to form a first mixed material, and the first mixed material is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode layer are stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature is 150°C, the hot pressing time is 10 minutes, and the hot pressing pressure is 120Mpa;

[0142] (2) Preparation of negative electrode: The negative electrode active materials graphite, (CMC+SBR), super-P and Li3YCl3Br3 are mixed evenly in a mass ratio of 69:4:2:25, placed in a high shear force equipment mixer, fiberized to form a second mixture, and the second mixture is rolled to form a first negative electrode layer; the rolling temperature is 60°C and the rolling time is 5 minutes; the negative electrode current collector and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode. The hot-pressing temperature is 120°C, the time is 12 minutes, and the pressure is 200MPa;

[0143] (3) Preparation of solid electrolyte membrane: The first halide solid electrolyte Li2ZrCl6 and the binder PTFE were mixed in a mass ratio of 90:10, and then pressed into a membrane;

[0144] (4) Bonding the positive electrode, the negative electrode and the solid electrolyte membrane to obtain an all-solid-state lithium battery.

[0145] Comparative Example 2

[0146] This embodiment provides a method for preparing an all-solid-state lithium battery, comprising the following steps:

[0147] (1) Preparation of positive electrode: NCM811, PTFE, super-P, and Li2ZrCl6 are mixed uniformly in a mass ratio of 70:3:2:25, placed in a high shear force equipment mixer, subjected to fiberization treatment, to form a first mixed material, and the first mixed material is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes; the positive electrode current collector and the first positive electrode layer are stacked, hot pressed, and cooled to form a composite positive electrode. The hot pressing temperature is 150°C, the hot pressing time is 10 minutes, and the hot pressing pressure is 120Mpa;

[0148] (2) Preparation of negative electrode: The negative electrode active materials graphite, (CMC+SBR), super-P and Li3YCl3Br3 are mixed evenly in a mass ratio of 69:4:2:25, placed in a high shear force equipment mixer, fiberized to form a second mixture, and the second mixture is rolled to form a first negative electrode layer; the rolling temperature is 60°C and the rolling time is 5 minutes; the negative electrode current collector and the first negative electrode layer are stacked, hot-pressed, and cooled to form a composite negative electrode. The hot-pressing temperature is 120°C, the time is 12 minutes, and the pressure is 200MPa;

[0149] (3) Preparation of solid electrolyte membrane: The first halide solid electrolyte Li2ZrCl6 and the binder PTFE were mixed in a mass ratio of 90:10, and then pressed into a membrane;

[0150] (4) Preparation of barrier layer powder: The second halide solid electrolyte Li6PS5Cl and the binder PTFE were mixed in a mass ratio of 90:10.

[0151] (5) Spraying the barrier layer powder onto the negative electrode, performing a heat pressing treatment to form a barrier layer, and obtaining an intermediate.

[0152] The thickness of the barrier layer is 10 μm, the temperature of the hot pressing treatment is 150° C., the pressure of the hot pressing treatment is 250 MPa, and the time of the hot pressing treatment is 10 min.

[0153] (6) The intermediate is bonded to a solid electrolyte membrane and a positive electrode to obtain an all-solid-state lithium battery.

[0154] The barrier layer is arranged at the negative electrode, on the side close to the solid electrolyte membrane.

[0155] Performance Testing

[0156] (1) Melting point test

[0157] The second halide solid electrolyte material was placed in a crucible and heated from 30°C to 300°C at a rate of 10°C / min in a nitrogen atmosphere to measure the melting point of the second halide solid electrolyte material.

[0158] (2) Porosity test

[0159] True density test: The true density of the composite positive electrode is obtained by testing with a true density meter. The test process is as follows: After the power is turned on, the instrument is preheated according to the requirements of the instrument manual to ensure that the instrument reaches a stable working state. Place the sample to be tested in the sample pool, press the measurement button, and the instrument will automatically measure the density. After the measurement is completed, the instrument will automatically record the data and calculate the true density value ρ 真 .

[0160] Compaction density test: 100 mg of powder was added to the mold, a pressure of 375 MPa was applied and maintained for 3 min, and then the mold was demolded to obtain a compacted sheet, its thickness was measured, and its compaction density ρcompacted was calculated.

[0161] Porosity: Porosity is (ρ 真 -ρ 压实 ) / ρ 真

[0162] (3) Ionic conductivity test

[0163] At 25° C., the ionic conductivity of the barrier layers of the embodiments and comparative examples was tested. The test results are shown in Table 1.

[0164] (4) Battery internal resistance test

[0165] At 25° C., a voltage internal resistance meter was used to measure the internal resistance of the all-solid-state lithium batteries in the embodiment and the comparative example. The test results are shown in Table 1.

[0166] (5) Discharge specific capacity test

[0167] The all-solid-state lithium battery in the embodiment and the comparative example was tested for capacity, left to stand for 1 min, and discharged at a discharge current of 0.1 C until the cut-off voltage was 2.7 V, and the first discharge capacity was recorded. The results are shown in Table 1 below.

[0168] (6) Cyclic performance test

[0169] The all-solid-state lithium battery in the embodiment and the comparative example was subjected to a cycle test. At a temperature of 25°C±2°C, the first step was to charge at 0.1C to a final voltage of 4.5V, a cut-off current of 0.05C, and stand for 30 minutes; the second step was to discharge at 0.1C to a final discharge voltage of 2.7V, record the discharge capacity, and stand for 30 minutes; the first and second steps were cycled to test the cycle performance of the battery for 500 cycles. The results are shown in Table 1 below.

[0170] Table 1

[0171]

[0172]

[0173] As shown in Table 1, by comparing Examples 1 to 5 and Comparative Examples 1 to 2, it can be seen that the all-solid-state lithium battery provided in the present application prepares a barrier layer with low porosity and high ion conductivity, which reduces the internal resistance of the battery, increases the initial discharge capacity, and improves the battery's cycle capacity retention rate.

[0174] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0175] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An all-solid-state lithium battery, characterized in that: It includes a positive electrode, a negative electrode, a solid electrolyte membrane and a barrier layer arranged between the negative electrode and the solid electrolyte membrane; The solid electrolyte membrane includes a first halide solid electrolyte, and the barrier layer includes a second halide solid electrolyte. The chemical formula of the second halide solid electrolyte is: Li3MCl 6-x Br x , where M is a trivalent metal ion, 0 <x<6; The second halide solid electrolyte in the barrier layer changes from solid to liquid, and then changes from liquid to solid.

2. The all-solid-state lithium battery according to claim 1, characterized in that: The Li3MCl 6-x Br x The melting point is 80℃~200℃.

3. The all-solid-state lithium battery according to claim 1, characterized in that: M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3 + 、Bi 3+ and one or more of trivalent lanthanide metals.

4. The all-solid-state lithium battery according to claim 1, characterized in that: The Li3MCl 6-x Br x The ionic conductivity λ satisfies: λ ≥ 1mS / cm.

5. The all-solid-state lithium battery according to claim 1, characterized in that: The porosity of the barrier layer is 0.1% to 10%; and / or, The thickness of the barrier layer is 2 μm to 20 μm.

6. The all-solid-state lithium battery according to any one of claims 1 to 5, characterized in that: The barrier layer further comprises a second component, and satisfies: the melting point of the second component is greater than the melting point of the second halide solid electrolyte; Preferably, the second component comprises one of a ceramic material and a polymer material.

7. The all-solid-state lithium battery according to any one of claims 1 to 5, characterized in that: The solid electrolyte membrane further includes the second halide solid electrolyte.

8. The all-solid-state lithium battery according to claim 7, characterized in that: The mass proportion of the second halide solid electrolyte in the solid electrolyte membrane is 5% to 40%.

9. A method for preparing an all-solid-state lithium battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of positive electrode, negative electrode and solid electrolyte membrane; Spraying or laying a barrier layer powder onto one of the negative electrode and the solid electrolyte membrane, and performing a hot pressing process to obtain an intermediate; Or, preparing a barrier layer, and subjecting the barrier layer and one of the negative electrode and the solid electrolyte membrane to a heat pressing process to obtain an intermediate; The intermediate is bonded to the other of the negative electrode and the solid electrolyte membrane and the positive electrode to obtain the all-solid-state lithium battery.

10. The method for preparing an all-solid-state lithium battery according to claim 9, characterized in that: The temperature of the hot pressing treatment is 120°C to 180°C; and / or, The heat pressing treatment time is 0.5min to 20min; and / or, The pressure of the hot pressing treatment is 10 MPa to 500 MPa.

Citation Information

Cited By

  • Solid-state battery cell, electrolyte sheet and preparation method therefor, battery apparatus, and electrical apparatus

    WO2026144744A1